Unscattering the burden of disease landscape: supporting interaction between existing burden of disease efforts. (30th September 2020) - Haagsma, J; Majdan, M; Pires, S M; Assunção, R
Abstract: The burden of disease landscape in Europe is currently scattered with experts from diverse professional backgrounds, ranging from experts in infectious diseases, non-communicable diseases, injuries and risk factors, to experts in more comprehensive national, regional and global burden of disease studies. Currently there is little interaction between these experts and existing burden of disease efforts. The European burden of disease network (burden-eu) COST Action aims to bring together expertise across different domains and professional backgrounds. During the course of the burden-eu COST Action, several steps will be taken to facilitate interaction between existing burden of disease efforts. First, a survey has been sent around to all members of the EU burden of disease network to map burden of disease studies that have been carried out in their country. Apart from general details about the year of the study and cause of disease categories, items of the survey included data sources, methodological approach and collaborations with institutes of other countries. In the first month, the survey has been completed for over 70 studies that have been carried out in twelve countries. Second, comparison of existing burden of disease initiatives allows for the identification of the various domains for which burden of disease has been assessed, highlight methodological differences as well as similarities, and facilitate improvements and harmonization of methods and approaches. Furthermore, the data collected from the survey will be included in a continuously updated burden of disease database that lists all past and current burden of disease activities. Lastly, burden-eu will facilitate regular meetings and workshops. Each of these steps will make it possible to move beyond the currently scattered burden of disease landscape and increase interaction between professionals and burden of disease efforts.